The Effect of Leadership, Principal Decision Making and Job Satisfaction on Teacher Performance at SMA Negeri 13 Palembang - Yuniarti, Yuniarti (Utan Kayu Publishing, 2022)
This study aims to determine the Effect of Leadership, Principal Decision Making and Job Satisfaction on Teacher Performance in SMA Negeri 13 Palembang. In this study the samples taken were all teachers with a total of 68 people as samples of trial and research data. In this study the sampling technique is done by using saturated sampling technique that is all the population is sampled, the regression equation Y=5,080+0,274X1+0,403X2+0,409X3+e From the results of this study there is a positive and significant influence of Leadership, Principal decision making and Job satisfaction simultaneously on Teacher Performance in SMA Negeri 13 Palembang as evidenced by the sig F value of 0.000 <? (0.05). There is a positive and significant influence of Leadership on Teacher Performance in SMA 13 Palembang with a sig t value of 0.034 <? (0.05). There is a positive and significant influence of school decision-making on teacher performance in SMA Negeri 13 Palembang with a sig t value of 0.027 <? (0.05). There is a positive and significant effect of job satisfaction on teacher performance in SMA Negeri 13 Palembang with a sig t value of 0.003 <? (0.05). Correlation (R) variables influence Leadership (X1), decision making of principals (X2) and job satisfaction (X3) together on Teacher Performance (Y) is 0.551 means that the relationship of Leadership, Principals' decision making and job satisfaction together the same with the Performance of Teachers in Palembang 13 Public High School shows a strong and positive correlation. The coefficient of determination (Rsquare) is 0.304 which gives an understanding that 30.4% of Teacher Performance (Y) can be explained or influenced by Leadership (X1), Principal decision making (X2) and Job satisfaction (X3) together while the rest is equal to 69.6% is influenced by other factors not examined.